TINJAUAN HUKUM ISLAM TERHADAP KERUGIAN YANG DISEBABKAN OLEH GHASAB DAN PENINGKATAN KESADARAN SANTRI TERHADAP PERILAKU GHASAB (STUDI KASUS DI PONDOK PESANTREN DARUL FALAH CERMEE BONDOWOSO) - Andi Susanto; Muhammad Abrori; Dina Sintia Bela; Aminatus Sadiah (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
The purpose of writing this article is to find out how the Islamic point of view answers the issue of ghasab that occurs in pesantren and increasing santri awareness of ghasab behavior. ghasab behavior. Methods and types of data collection in this research is to use a qualitative approach of the case study type. The results The results showed that ghasab behavior occurred due to two forms of deviation, the first is individual deviation. deviation, the first is individual deviation, ghasab behavior occurs due to lack of awareness, lust for revenge, and social conditions. behavior occurs due to lack of awareness, lust for revenge, and social and cultural conditions that affect the psychology of students. cultural conditions that affect the psychology of santri. Second, deviation situational deviation, ghasab behavior occurs due to urgent situations, and the opportunity to ghasab. there is an opportunity for ghasab. There are prevention efforts that There are prevention efforts made by the Darul Falah Islamic Boarding School in Ramban Kulon Cermee Bondowoso. These prevention efforts can be divided into two, first: Prevention Prevention in the form of regulations such as the prohibition of ghasab in the form of posters and rules contained in the santri handbook. contained in the santri guidebook. Second, in the form of indirect prevention indirect prevention through the education of learning boarding books, fulfillment of facilities, and positive boarding school activities, facilities, and positive boarding school activities. Keywords: Islamic Law, Ghasab, Pesantren.